The Effectiveness of Using Kahoot Games to Improve Students Vocabulary at Junior High School - Rochman, Mochammad Iman Nur; Ulfah, Maria; Ma’rifatullah, Sayid (Bilingua, 2024)
There are a lot of problems in the education today that are connected to societal change and technology advancement. In the present day, the number of digital natives, or at last second-generation traditions, is growing. These are people that consider their environment to be the digital one they have been a part since birth. Many research investigations have demonstrated how game-based learning encourage students to actively participate in class because it makes them feel good. This study is aim to investigate how well Kahoot works for teaching vocabulary in English. The data for this descriptive qualitative study was collected using a literature review methodology. According to the results, students though that teaching English in the classroom with Kahoot was a good idea. By using a gamification technique, the advancement of technology can be used inside of the classroom